Dual-curing resin cement with colour indicator for adhesively cemented restorations to dental tissues: Change of colour by curing and some physical properties - Aki Niemi; Leila Perea-Lowery; Samer M.Alaqeel; Ravikumar Ramakrishnaiah; Pekka K. Vallittu (King Saud University, 2022)
The study was aimed to investigate a color indicator containing dual curing resin composite luting cement and to plot the color change to the time of solidification of the cement. In addition some physical properties were studied. Specimens were made of a dual-cure resin cement (Maxcem Elite™ Chroma, Kerr, Orange, CA, USA) and polymerized by autopolymerization only, or with light initiated polymerization. A spectrophotometer was used to quantify the color change of the cement as plotted with the curing time. The efficacy of the curing process was studied by measuring water sorption and the ultimate flexural properties of the cement. The results showed that the flexural strength of cement after autopolymerization was 27.3 MPa and after light initiated polymerization 48.1 MPa. Young's modulus of bending was 2089.3 MPa and 3781.5 MPa respectively for the same cement samples. Water sorption after two weeks for the autopolymerization cement samples was -1.12 wt% and for the light initiated polymerization samples 0.56 wt%. Non-parametric Spearman's correlation was measured for autopolymerized cement samples between variables for color and solidification load (N), which showed a strong correlation between curing process and color change (p < 0.05). There was a correlation between the color change and degree of monomer conversion of the dual curing resin composite luting cement which contained a color indicator system for polymerization reaction. The study also suggested that autopolymerization only resulted in suboptimal polymerization of the cement. By additional light curing considerably higher flexural properties were obtained.